Corporate socially responsible investments: CEO altruism, reputation, and shareholder interests - Borghesi, Richard; Houston, Joel F.; Naranjo, Andy (Journal of Corporate Finance, 2014)
Corporate managers often invest in activities that are deemed to be socially responsible. In some instances, these investments enhance shareholder value. However, in other cases, altruistic managers or managers who privately benefit from the positive attention arising from these activities may choose to make socially responsible investments even if they are not value enhancing. Given this backdrop, we investigate the various factors that motivate firm managers to make socially responsible investments. We find that larger firms, firms with greater free cash flow, and higher advertising outlays demonstrate higher levels of corporate social responsibility (CSR). We also find that companies with stronger institutional ownership are less likely to invest in CSR — which casts doubt on the argument that these investments are designed to promote shareholder value. Consistent with the literature that explores how CEO personal attributes influence corporate decision making, we find that female CEOs, younger CEOs, and managers who donate to both Republican and Democratic parties are significantly more likely to invest in CSR. This latter result suggests that CSR investments may not be driven solely for altruistic reasons, but instead may be part of a broader strategy to create goodwill and/or help maintain good political relations. Finally, we find a strong positive connection between the level of media scrutiny surrounding the firm and its CEO, and the level of CSR investment. This finding suggests that media attention helps induce firms to make socially responsible investments.